2019
DOI: 10.21608/ejfs.2019.18646.1026
|View full text |Cite
|
Sign up to set email alerts
|

Production and evaluation of stirred synbiotic fermented milk fortified with fig fruit

Abstract: T HE OBJECTIVE of this study was to produce stirred probiotic fermented milk fortified with fig (Ficus carica L.) to be a source of milk ingredients like milk protein, calcium, magnesium, vitamin B12 and probiotic bacteria. In addition to rich fruit ingredients such as dietary fiber, polyphenols, antioxidants and different minerals. Therefore, figs puree was added to the milk (5, 10 and 20%) and the results obtained showed that, samples of T3 (with 20% fig puree) have the highest values for dietary fiber and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In Rayeb milk samples, all extracts had a nonsignificant ( p > 0.05) effect on their sensory parameters but were still accepted by panelists. This was in agreement with the results of previous studies [ 1 , 3 , 24 ]. The samples of Rayeb had a more balanced taste and were more accepted than the same concentrations in pasteurized milk samples; this agreed with the study results of Tami et al [ 25 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…In Rayeb milk samples, all extracts had a nonsignificant ( p > 0.05) effect on their sensory parameters but were still accepted by panelists. This was in agreement with the results of previous studies [ 1 , 3 , 24 ]. The samples of Rayeb had a more balanced taste and were more accepted than the same concentrations in pasteurized milk samples; this agreed with the study results of Tami et al [ 25 ].…”
Section: Resultssupporting
confidence: 94%
“…1A and B ). The increasing milk acidity may be referred to as sugar fermentation, which increases in alcoholic extracts of used dried fruits due to high sugar concentrations [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was shown that M. indica in yogurt formulations substantially improves the flavor during sensory evaluation despite containing stevia (Parra Huertas et al, 2016). In another study, it was shown that the enrichment of fermented milk with fig puree in different proportions (5, 10 and 15%) was sensorially acceptable, despite the fact that the pH decreased (5.34 to 4.43) and the acidity increased (0.48 to 0.77%), in this sense; the addition of fruit at an optimal level improves the sensory quality, physical-chemical and rheological properties of the yogurt (Abd-Eltawab, 2019).…”
Section: Organoleptic Characteristics Of Yogurt From Mangifera Indica...mentioning
confidence: 99%
“…However, employing the permeate has economic relevance since it is regarded useful alternative to skim milk as partial or entire replacement [12]. Fig and kiwi are rich sources of sugar, organic acid, mineral, vitamins, polyphenols, flavonoids and fiber [13,14]. They found that fruity milk residue is rich source of important electrolytes.…”
Section: Introductionmentioning
confidence: 99%